Cloning, expression and phylogenetic analysis of IFN-Î³ gene in chicken - CHATURVEDI, UTTARA; KALIM, SHAHINA; SINGH, LAKSHYA VEER; SAHOO, A P; PALIA, S K; KUMAR, RAJIV; KUMAR, G RAVI; TIWARI, SANGEETA; TIWARI, ASHOK K (The Indian Journal of Animal Sciences, 2013)
In the present study, chicken interferon gamma (Ch.IFN-Î³) gene was amplified using specific primers by RT-PCRand cloned into pTZ 57R/T cloning vector. The clone was confirmed by restriction digestion analysis using KpnI andApaI restriction enzymes and orientation was confirmed by colony PCR using T7 promoter primer and gene specificforward primers. Further, the gene fragment was sub-cloned in eukaryotic expression vector pcDNA 3.1(+) and confirmedby restriction digestion. The recombinant pcDNA 3.1 having IFN gene (pcDNA.Ch-IFN-Î³) was checked for its abilityto express IFN-Î³ in vitro in cell culture and expression was confirmed by RT-PCR, indicating the gene is functionallyactive. The study to evaluate ability of pcDNA.Ch-IFN-Î³ to combat infection and enhance efficacy of DNA vaccine isunder way.